PENERAPAN SERTIFIKASI FOREST STEWARDSHIP COUNCIL (FSC) SEBAGAI UPAYA PENINGKATAN DAYA SAING ECO-PRODUCT DI KAWASAN ASIA-PASIFIK - Zuha, Aulia Aisyah (Indonesian Association for International Relations, 2024)
This research explains efforts to increase the competitiveness of eco-products in the Asia-Pacific region through the implementation of Forest Stewardship Council (FSC) certification for processed forest products in the Asia-Pacific. A descriptive qualitative research method of literature study, as well as a pluralism approach and an international private regime perspective were used. The research results show that FSC offers a reliable solution for sustainable forest management through the implementation of two certifications, namely Chain of Custody (COC-FSC) and Forest Management (FM-FSC) which can help all interest groups to convince consumers that their production comes from processed wood. sourced from forests that are responsible both from an environmental, economic and social perspective. This FSC certification can increase the competitiveness of eco-products in the Asia-Pacific region